Games as Distributed Teaching and Learning Systems. Issue 12 (November 2017) - Gee, Elisabeth; Gee, James Paul
Background: Videogames and virtual worlds have frequently been studied as learning environments in isolation; that is, scholars have focused on understanding the features of games or virtual worlds as separate from or different than "real world" environments for learning. Although more recently, scholars have explored the teaching and learning that take place around games and virtual worlds, for example, in affinity spaces, these too have been treated as separate and often divorced from other learning experiences. Purpose: Our goal in this article is to describe learning from experience, the nature of digital games, and distributed systems of teaching and learning in an integrated way that transcends dichotomies of online and offline activities or spaces. Research Design: This article offers a theoretical framework in which to understand some aspects of teaching and learning outside of school today. Drawing on contemporary theories of how the mind works, we identify the central role of embodied experience in human thought and learning. We use videogames as examples of how real and virtual experiences are mediated in similar ways by good tools and social interactions. We argue that videogames and virtual worlds offer opportunities for new types of "conversations" with other people, with virtual worlds, and with the "real" world, conversations that extend humans' abilities to learn from experiences. We then examine how experiences with games and virtual worlds are located and interpreted within broader, dynamic systems of social relations, technologies, practices, teaching, and learning. Conclusions: Understanding our experiences with videogames and virtual worlds as distinctive forms of conversations with the world, situated within distributed teaching and learning systems, offers us a new means of understanding their potential significance in people's lives for learning, belonging, and problem solving.